The Arabidopsis EDR1 Protein Kinase Negatively Regulates the ATL1 E3 Ubiquitin Ligase to Suppress Cell Death. Issue 11 (14th November 2014) - Serrano, Irene; Gu, Yangnan; Qi, Dong; Dubiella, Ullrich; Innes, Roger W.
Abstract : ATL1 is a ubiquitin ligase that promotes cell death, but this activity is inhibited by the protein kinase EDR1, which physically associates with ATL1. Loss of EDR1 function enhances cell death in response to biotic and abiotic stresses; thus, stress-induced cell death signaling is regulated by two major and interlinked posttranslational modification mechanisms: phosphorylation and ubiquitination. Abstract: Loss-of-function mutations in the Arabidopsis thaliana ENHANCED DISEASE RESISTANCE1 ( EDR1 ) gene confer enhanced programmed cell death under a variety of abiotic and biotic stress conditions. All edr1 mutant phenotypes can be suppressed by missense mutations in the KEEP ON GOING gene, which encodes a trans -Golgi network/early endosome (TGN/EE )-localized E3 ubiquitin ligase. Here, we report that EDR1 interacts with a second E3 ubiquitin ligase, ARABIDOPSIS TOXICOS EN LEVADURA1 ( ATL1 ), and negatively regulates its activity. Overexpression of ATL1 in transgenic Arabidopsis induced severe growth inhibition and patches of cell death, while transient overexpression in Nicotiana benthamiana leaves induced cell death and tissue collapse. The E3 ligase activity of ATL1 was required for both of these processes. Importantly, we found that ATL1 interacts with EDR1 on TGN/EE vesicles and that EDR1 suppresses ATL1-mediated cell death in N. benthamiana and Arabidopsis . Lastly, knockdown of ATL1 expression suppressed cell death phenotypes associated with the edr1 mutant and made Arabidopsis hypersusceptible to powdery mildew infection. Taken together, our data indicate that ATL1 is a positive regulator of programmed cell death and EDR1 negatively regulates ATL1 activity at the TGN/EE and thus controls stress responses initiated by ATL1-mediated ubiquitination events.